The Impact of Ease of Doing Business on Economic Growth: Evidence from a Two-Way Fixed Effects (TWFE) Model - Mohamad Egi Destiartono (Future Academia : The Journal of Multidisciplinary Research on Scientific and Advanced, 2026)
This study intends to examine the linkage between ease of doing business (eodb) and economic growth within the framework of the neoclassical growth model, considering the role of capital formation. The analysis relies on a panel dataset of 111 countries covering the period 2015–2019. All data were obtained from the the World Bank. The Two-Way Fixed Effects (TWFE) estimator is applied to account for both country-specific and time-specific heterogeneity. Additionally, the hierarchical regression is utilized to assess the robustness and consistency of the estimated parameters. The findings of TWFE indicate that both gross fixed capital formation per capita and the ease of doing business index are positively associated with GDP per capita. These results confirm that capital formation and a favorable business environment serve as important drivers of economic growth. Therefore, it is pivotal continue to promote investment and implement regulatory reforms that improve the business environment in order to foster sustained economic growth.